Primerjava prednosti in slabosti volilnih sistemov - Ribičič, Ciril (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2013)
The author compares three electoral systems with each other and with the current Slovenian electoral system. The strengths and weaknesses of the absolute (two-round) majority system, the proportional electoral system with a preferential vote and the mixed-member proportional system are also discussed in light of the current political and economic crisis in Slovenia. The majority system, on the one hand, ensures greater stability of the government but lacks proper (majoritarian) legitimacy. It is thus unacceptable in terms of the present economic crisis in which the government needs convincing legitimacy as well as because of its inherent quality of polarizing the political landscape. On the other hand, the lack of influence of the voters on which candidates will be elected (personalization) in proportional system, is particularly inappropriate in light of the serious discontent of the protesters with the current lack of political legitimacy of the political parties. Therefore, the author favors the introduction of the combined electoral system which combines the strengths of both previous systems.
Keywords: election; volitve; volilni sistemi